CLINICAL AND ANGIOGRAPHIC CHARACTERISTICS OF TAKAYASHU'S ARTERITIS:- PATIENT REPORT - Miljković, Dušan (Acta medicae Medianae, 2025)
Takayashu’s arteritis is a chronic, immune-mediated vasculitis of the large blood vessels, which usually occurs in patients younger than 50 years and primarily affects the aorta and its main branches. The majority of affected are women. A patient with Takayashu's arteritis who first visited the doctor due to fatigue, palpitations and rapid heart rate is presented. On clinical examination, over both carotid arteries, audible murmurs, the pulse of the right radial artery is very weak, and the pulse of the left radial artery is not palpable. Laboratory analyzes revealed increased sedimentation of erythrocytes and the level of C-reactive protein. The diagnosis of the disease was confirmed by Doppler ultrasound of blood vessels, computed tomography angiography (CTA) and positron emission tomography (18 F-FDG PET/CT). The patient fulfilled five out of six criteria for the clinical diagnosis of Takayashu’s arteritis of the American College of Rheumatology and belonged, according to the angiographic and clinical classification of Takayashu’s arteritis, to Type I. She was treated with corticosteroids, immunosuppressants and percutaneous transluminal angioplasty.
Keywords: Takayashu’s arteritis, Macaroni sign, Doppler of blood vessels, Multislice computed tomography, positron emission tomography / computed tomography